Person-centred care for dementia patients (backend system) - Liang, Zhiheng (Nanyang Technological University, 2023)
Dementia is a neurological disorder which impacts cognitive functions and affects millions worldwide. It has multiple underlying causes, such as Alzheimer’s disease and stroke, which bring significant challenges to individuals and their caregivers. Due to the high demand for caregiving, dementia care centres are facing a lack of manpower, making it challenging to provide adequate care for patients. The Person-Centred Care (PEAR) system was developed to lessen the workload of person-centred care workers while simultaneously improving the quality of care. This system is available on both web and mobile platforms, ensuring convenience for caregivers and doctors who prefer mobile access while providing a web interface for other users. This report focuses on the implementation of web applications for the supervisor role utilizing the MVC framework, the creation of the relevant APIs based on user requirements, and the formulation of the API test cases using the .NET associated libraries including MyTested.AspNetCore.Mvc, Xunit and Moq. Additionally, it also addresses the documentation of API and system structures.